A Techno-Economic Analysis of Solar Energy Developmental Under Competing Technologies: A Case Study in Jiangxi, China. (June 2022) - Rafiq, Muhammad Aftab; Zhang, Liguo; Kung, Chih-Chun
Energy sustainability, as well as climate change mitigation, is an immediate challenge facing the world, especially for large developing countries such as China and India. This study analyses the solar photovoltaic (PV) potential of Jiangxi, China, using three dominant technologies including conventional PV, PV/PCM (Phase Change Material), and PV/T-PCM (Thermal-Phase Change Material). We employ a lifecycle assessment by investigating the spatial differences of radiation conversion rates across major cities. Two sets of scenario analyses are also examined: (1) fixed installation capacity; and (2) fixed government investment. Each set has three alternative scenarios to distinguish the power generation potential, investment requirement. The results show that under the "fixed capacity" scenarios, the conventional PV can generate 313 GWh/year, and the PV/T-PCM can yield more than 340 GWh/year. The result would change substantially under the "fixed investment" scenarios, in which the annual solar power from conventional PV is more than 1, 736 GWh. The scenario analysis points out that if the total investment rather than total capacity is fixed, the power generation from solar PV systems can be maximized, but the total cost would increase considerably as well. Amortization of the installation costs that would potentially alleviate the firms' fiscal burden is also discussed.